THE EFFECT OF INCENTIVES AND WORK FACILITIES ON TEACHERS' WORK MOTIVATION AT THE AL-KARIM EDUCATION FOUNDATION MORAWA CAPEX - Safira Aisya Ulyasari; Sri Gustina Pane; Julkarnain (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is to determine the effect of incentives and work facilities on teacher work motivation at the Al-Karim Tanjung Morawa Education Foundation. This study uses a quantitative method, data sources are obtained from secondary data, namely respondent data and primary data sources, namely interviews, observations and questionnaires distributed directly to respondents. The population in this study were 35 teachers at the Al-Karim Tanjung Morawa Education Foundation, sampling using non-probability sampling techniques with saturated samples because the research population is relatively small. The data analysis method uses validity and reliability tests to determine the accuracy of the measuring instruments used in the study, then classical assumption tests, multiple linear regression tests and hypothesis tests are tested using SPSS version 27. The results of this study indicate that incentives have a positive and significant effect on teacher work motivation at the Al-Karim Tanjung Morawa Education Foundation, work facilities have a positive and significant effect on teacher work motivation at the Al-Karim Tanjung Morawa Education Foundation, and incentives and work facilities simultaneously have a positive and significant effect on teacher work motivation at the Al-Karim Tanjung Morawa Education Foundation.